How does an athlete`s heart react to studying at university? - Popova, T.; Koriukalov, Y.; Kourova, O.; Gurlev, V.; Khomykova, T. (BIO Web of Conferences, 2020)
2 groups of participants have been studied: I - student-athletes; II - students and postgraduate students, not involved in sport. The functional status of the heart has been studied in three conditions: at rest, during the cognitive test, and under local static load (the wrist dynamometer). The electroencephalography has also been applied. Results demonstrated a statistical decrease in wrist endurance in all participants during the academic year. They proved fatigue development. A pronounced increase of heart rate and arterial blood pressure, as well as the increase of heart rate variability mode and stress index under local load and during the cognitive test, proved the development of the heart functional stress, especially in athletes. Electroencephalography data prove the central origin of adaptation reactions both to mental and to local muscular activity. Disease prevention and health improvement measures are necessary for university students actively involved in sport. One of such measures is relaxation exercises aimed at a decrease in functional stress.